Oxidative mitigation of aquatic methane emissions in large Amazonian rivers - Henrique O. Sawakuchi; David Bastviken; André O. Sawakuchi; Nicholas D. Ward; Clovis D. Borges; Siu M. Tsai; Jeffrey E. Richey; Maria Victoria R. Ballester; Alex V. Krusche (Global Change Biology, 2016)
The flux of methane ( CH 4 ) from inland waters to the atmosphere has a profound impact on global atmospheric greenhouse gas ( GHG ) levels, and yet, strikingly little is known about the dynamics controlling sources and sinks of CH 4 in the aquatic setting. Here, we examine the cycling and flux of CH 4 in six large rivers in the A mazon basin, including the A mazon R iver. Based on stable isotopic mass balances of CH 4 , inputs and outputs to the water column were estimated. We determined that ecosystem methane oxidation ( MOX ) reduced the diffusive flux of CH 4 by approximately 28–96% and varied depending on hydrologic regime and general geochemical characteristics of tributaries of the Amazon River. For example, the relative amount of MOX was maximal during high water in black and white water rivers and minimal in clear water rivers during low water. The abundance of genetic markers for methane‐oxidizing bacteria ( pmoA ) was positively correlated with enhanced signals of oxidation, providing independent support for the detected MOX patterns. The results indicate that MOX in large Amazonian rivers can consume from 0.45 to 2.07 Tg CH 4 yr −1 , representing up to 7% of the estimated global soil sink. Nevertheless, climate change and changes in hydrology, for example, due to construction of dams, can alter this balance, influencing CH 4 emissions to atmosphere.

Methane emissions from Amazonian Rivers and their contribution to the global methane budget - Henrique O. Sawakuchi; David Bastviken; André O. Sawakuchi; Alex V. Krusche; Maria V. R. Ballester; Jeffrey E. Richey (Global Change Biology, 2014)
Methane ( CH 4 ) fluxes from world rivers are still poorly constrained, with measurements restricted mainly to temperate climates. Additional river flux measurements, including spatio‐temporal studies, are important to refine extrapolations. Here we assess the spatio‐temporal variability of CH 4 fluxes from the Amazon and its main tributaries, the Negro, Solimões, Madeira, Tapajós, Xingu, and Pará Rivers, based on direct measurements using floating chambers. Sixteen of 34 sites were measured during low and high water seasons. Significant differences were observed within sites in the same river and among different rivers, types of rivers, and seasons. Ebullition contributed to more than 50% of total emissions for some rivers. Considering only river channels, our data indicate that large rivers in the Amazon Basin release between 0.40 and 0.58 Tg CH 4 yr −1 . Thus, our estimates of CH 4 flux from all tropical rivers and rivers globally were, respectively, 19–51% to 31–84% higher than previous estimates, with large rivers of the Amazon accounting for 22–28% of global river CH 4 emissions.